Use and aesthetics of Iasian marble in presbyteries of the 6th century - Diego Peirano (Polish Archaeology in the Mediterranean, 2023)
This paper offers a survey of the uses of Iasian marbles and their relationships with other stones. In the 6th century, these marbles were used for wall cladding and flooring, with an aim to alternate with or frame lighter marbles, as was the case in Iasos, in the Agora Basilica. Similar combinations were attested in the cladding of synthronoi of the basilicas A and C of Nea Anchialos. In the latter, the sides of the presbytery were framed with red cipollino slabs of different lengths and widths. In the prostoon, verde antico was added to red and white veined marbles.Other examples seem to demonstrate the use of the red cipollino to mark thresholds and passageways, as was the case of the solea of Hagia Sophia and the presbytery of the basilica of St. John in Ephesos. There, the templon stylobate and bases made of Iasian marble supported columns of verde antico and gray marbles; some slabs would have been of the openwork type; thus, the variety of marbles, their textures and workmanship must have contributed to the deep impact of the arrangement.